2017
DOI: 10.1155/2017/8271042
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Concept of Degrees of Maternal Morbidity as a Tool for Surveillance of Maternal Health in Latin American and Caribbean Settings

Abstract: Objectives To assess a birth registry to explore maternal mortality and morbidity and their association with other factors. Study Design Exploratory multicentre cross-sectional analysis with over 700 thousand childbirths from twelve Latin American and Caribbean countries between 2009 and 2012. The WHO criteria for maternal morbidity were employed to split women, following a gradient of severity of conditions, into (1) maternal death (MD); (2) maternal near miss (MNM); (3) potentially life-threatening condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 24 publications
(41 reference statements)
2
18
0
8
Order By: Relevance
“…The systematic monitoring of severe maternal morbidity through indicators of potentially life-threatening maternal conditions is also suggested as an important strategy to understand their determining factors and to intervene in them in a timely manner. The development of improved care technologies can significantly reduce maternal morbidity 38,[40][41][42] . Finally, this study's results support a deeper analysis of the phenomena of IPV and severe maternal morbidity as a priority to qualify the integral health care provided to women.…”
Section: Fewer Than Nine Years Referencementioning
confidence: 99%
“…The systematic monitoring of severe maternal morbidity through indicators of potentially life-threatening maternal conditions is also suggested as an important strategy to understand their determining factors and to intervene in them in a timely manner. The development of improved care technologies can significantly reduce maternal morbidity 38,[40][41][42] . Finally, this study's results support a deeper analysis of the phenomena of IPV and severe maternal morbidity as a priority to qualify the integral health care provided to women.…”
Section: Fewer Than Nine Years Referencementioning
confidence: 99%
“…In a study in Latin American maternity hospitals, C-sections were associated with an increased risk of SMO even after controlling for confounding variables. [ 21 ] In a Brazilian study, C-section was not associated with a risk of SMO in women with hypertensive disorders in general. [ 34 ] A randomized clinical trial conducted in a tertiary hospital in India reported similar findings, with maternal outcome being slightly, although not significantly, better with C-sections.…”
Section: Discussionmentioning
confidence: 99%
“…23 Therefore, early identification of morbidities before pregnancy, adequate management with the necessary attention, and caution may be a way to interrupt the spectrum of morbidity leading to severity, dysfunction, and death. 4,24,25 It is believed that postpartum surveillance after a SMM event should be individualized, that its duration will depend on the stabilization or resolution of the woman's condition, and that it should be performed by skilled health professionals depending on the resource context.…”
Section: Discussionmentioning
confidence: 99%